Experimental study to identify common engine part load conditions between Malaysian city driving and NEDC test - Zahari, I.; Abas, M. A.; Mat Arishad, N. I.; Zainal Abidin, S. F.; Muhamad Said, M. F. (Praise Worthy Prize, 2013)
This paper describes an experimental study conducted to identify the common engine part load conditions between Malaysian city driving and NEDC (New European Driving Cycle) test on a 4 cylinder gasoline fuelled engine, with multi-point fuel injection system, and continuous variable transmission vehicle. This is to pinpoint a regional area from the part load map in the attempt to strategize key technologies such as CDA (Cylinder Deactivation) or CNG (Compressed Natural Gas). Technologies such as CDA or CNG do not operate at all engine operations. Due to certain drawbacks, the operation of the technologies must be strategized to obtain most benefit from the engine. With the knowledge of the common part load region, these technologies could be integrated and strategized into the region to reduce overall fuel consumption. With improvements in fuel consumption respective to the identified common part load operations, the overall fuel consumption benefit does not only serve the legislation but also most importantly benefit the local consumers who travel on Malaysian roads. Copyright © 2009 Praise Worthy Prize S.r.l. - All rights reserved.